Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Ud. Jaya Abadi Probolinggo - Agung Yatiningrum; Yekti Rahajeng; Leni Dian Susanti; Fani Putri Wahidah; Achmad Maulidi (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of brand image and product quality on purchasing decisions at UD. Jaya Abadi partially. The research method used in this study is a quantitative research method using a sample of 100 consumers of UD. Jaya Abadi. The independent variables in this study are brand image and product quality with purchasing decisions as the dependent variable. Sampling using incidental sampling technique. The data analysis method used in this research is the primary data distribution of the questionnaire. Data processing is done using SPSS computer software. The results of the validity and reliability test showed that r arithmetic > r table, and from the overall number showing the Cronbach Alpha value > 0.60 it was stated that all variables in the reliability research test were declared reliable. Based on the T-test, the results of t count 4.664 > t table 1.985 and sig value 0.000 <0.05 which means that there is an influence of brand image on purchasing decisions at UD. Jaya Abadi and t count 2.602 > t table 1.985 and sig 0.011 <0.05 which means it means that there is an influence of product quality on purchasing decisions at UD. Jaya Abadi